Comedy tonight! - Malarcher, Jay, 1960- (Theatre symposium, 2008)
For centuries scholars, philosophers, and practitioners have attempted to explain just what constitutes comedy, and though no one has come close to a definitive explanation, each attempt highlights some distinct facet of the genre--the genre that Woody Allen has said eats at the childrens table ... even in the world of scholarship. The essays gathered in Volume 16 of the annual journalTheatre Symposiumillustrate well the range of material that falls under the heading comedy as it is played on stage. Stanley Longmans essay on The Commedia dellArte as the Quintessence of Comedy introduces us to the inhabitants of Commediatown, character types who are descendents of the Greeks and ancestors, it seems, of almost everyone who came after. Boris Senker, an eyewitness to Croatias evolution from communism to democracy, reports on the all-too-real "Commedia" stereotypes that have found their way onto the stage in his homeland. Other essays address the improvisational nature of "Commedia"; the roots of laughter and the expectations inherent in presenting old schtick to a new generation; comedic technique, verbal and physical, in Molière; the use of the macabre to create humor in the "Théâtre du Grand Guignol"; the story of Henry Fielding, the theatre practitioner most responsible for the British governments crackdown on subversive material, via the Licensing Act of 1737; Becketts theatrical connections to the comedy theory of Henri Bergson; and do-it-yourself (DIY) comedy--happenings, situations, gatheringsas practiced in British stand-up comedy. Theatre Symposium: Volume 16provides just a glimpse into the possibilities for comedy on the stage. If the past examples allow for extrapolation into the future, the position of comedy as a means of communicating problems and solutions for societys woes is remarkably sound.